PENGAWETAN TIGA JENIS KAYU SECARA RENDAMAN DINGIN DENGAN BAHAN PENGAWET BORAKS DAN ASAM BORAT - Sasa Abdurrohim (Jurnal Penelitian Hasil Hutan, 1994)
Wood samples  of three species measuring .3 cm x  3 cm x 3 cm (150 samples for each species) were treated with cold soaking treatment using borax and boric acid preservatives for 1,3,5,  7, and 9 days at the concentrations of 2,3, and 5 percent.The test result of experiment, after taking both retention and penetration  requirements into consideration for wood used under roof without ground contact showed that only  two species,  damar kunyit and pulai, could be satisfactorily treated with Boric Acid under the experimental  conditions,   while other species,  benuang,  couldn't  meet the standard.  Borax preservative  showed  a good result only on one species.  i.e.  pulai.For under roof usage without ground contact, pulai can be consecutively soaked for 9 and 7 days in boric acid solution of 3 and 5 percent, while in borax, for 5 and 3 days soaking  time are 3 and 5 percent. Damar kunyit used under roof without ground contact could be soaked for 7 days in boric acid solution of 5 percent.